Effects of Replacing Dietary Antibiotic Supplementation with Chitosan Levels on Rumen Metabolism and Nitrogen Use in Finishing Steers Fed Forage-Free Diets - Silva, T. I. S.; de Goes, R. H. T. B.; Cônsolo, N. R. B.; Gandra, J. R.; Osmari, M. P.; Silva, C. C.; Oliveira, L. E. F.; Souza, T. M.; Barbosa, L. C. G. S.; Anschau, D. G.; Silva, G. K. R.; Lopes, L. B.; Fernandes, J. W. S. (Faculty of Animal Science, IPB University, 2024)
The aim of this study was to evaluate the effects of replacing antibiotics with increasing doses of chitosan (CHI) on nutrient intake and digestibility, corn grain excretion, ruminal fermentation, nitrogen metabolism, and feeding behavior in finishing steers fed forage-free diets. Five ruminally cannulated crossbred steers were assigned to a 5 x 5 Latin square experimental design and given the following diets: C0= basal diet with no additives, ANT= basal diet with inclusion of virginiamycin 30 mg/kg DM, C375= basal diet with inclusion of chitosan 375 mg/kg DM, C750= basal diet with inclusion of chitosan 750 mg/kg DM, and C1500= basal diet with inclusion of chitosan 1500 mg/kg DM. Supplementation with CHI did not affect ruminal pH and ammonia nitrogen (N-NH3) concentration. Chitosan quadratically affected corn grain excretion and molar proportion of ruminal butyrate, with greater values for C750. Animals fed C375 showed greater dry matter intake and neutral detergent fiber intake; and greater digestibility of DM, starch, and NDF. Animals fed C750 and C1500 diets presented greater absorbed N compared to ANT. Animals fed ANT, C750, and C1500 spent more time eating and chewing than animals fed CON. More specifically, the dose of 375 mg/kg DM of diet was very promising for steers fed free-forage diet due to its ability to improve nutrient digestibility, with only slight changes in N metabolism.